Genetic Differences of Three Pollicipes mitella Populations Identified by PCR Analysis - Song, Young-Jae (Dev Reprod, 2013)
Genomic DNAs were extracted from the turtle leg (Pollicipes mitella, 1798) population of Tongyeong, Yeosu and Manjaedo located in the southern sea of Korea. The turtle leg population from Tongyeong (0.929) exhibited higher bandsharing values than did turtle leg from Manjaedo (0.852). The higher fragment sizes (>1,200 bp) are much more observed in the Yeosu population. The number of unique loci to each population and number of shared loci by the three populations, generated by PCR using 7 primers in the turtle leg (P. mitella) population of Tongyeong, Yeosu and Manjaedo. Genetic distances among different individuals of the Tongyeong population of the turtle leg (lane 1-07), Yeosu population of the turtle leg (lane 08-14) and Manjaedo population of the turtle leg (lane 15-21), respectively, were generated using the CLASSIFICATION option in Systat version 10 according to the bandsharing values and similarity matrix. The dendrogram, obtained by the seven decamer primers, indicated three genetic clusters: cluster 1 (TONGYEONG 01-TONGYEONG 07), cluster 2 (YEOSU 08-YEOSU 14), and cluster 3 (MANJEDO 15-MANJEDO 21). Tongyeong population could be evidently discriminated with the other two Yeosu and Manjaedo populations among three populations. The longest genetic distance (0.305) was found to exist between individuals’ no. 02 of the Tongyeong population and no. 13 of the Yeosu population. It seems to the authors that this is a result of a high degree of inbreeding in narrow region for a long while.